Effectiveness and safety of weekly therapy versus 3-weekly therapy of paclitaxel plus carboplatin in women with ovarian cancer: a protocol of systematic review and meta-analysis. Issue 3 (16th March 2022) - Qiu, Weitao; Fu, Yu; Dang, Yun; Cai, Bingxin; Tuo, Shumei; Mao, Baohong; Lin, Ru; Liu, Qing; Li, Yilin
Abstract : Introduction: Network meta-analyses have confirmed that paclitaxel plus carboplatin could improve progression-free survival (PFS) and overall survival (OS) compared with platinum alone. However, detailed implementation schedule (weekly or 3-weekly therapy) was not specified in clinical practice guidelines. Evidence from studies is also inconsistent. We will conduct a systematic review and meta-analysis to evaluate the benefits and harms of weekly therapy and 3-weekly therapy of paclitaxel combined with carboplatin in women with ovarian cancer. Methods: We will search PubMed, EMBASE and the Cochrane Library databases to include relevant randomised controlled trials comparing weekly therapy versus 3-weekly therapy of paclitaxel combined with carboplatin for women with ovarian cancer. Random-effects model will be used to pool data for patient-reported outcomes including survival rate, OS, PFS and adverse events. Grading of Recommendation, Assessment, Development and Evaluation approach will be used to rate the quality of evidence. Ethics and dissemination: This systematic review and meta-analysis will be based on published data and does not therefore require specific ethical approval or consent for participation. The results will be published in a peer-reviewed journal. OSF registration number: 10.17605/OSF.IO/GJUMA.